Evaluation of response after neoadjuvant treatment in soft tissue sarcomas: the European Organization for Research and Treatment of Cancer - Soft Tissue and Bone Sarcoma Group (EORTC-STBSG) recommendations for pathological examination and reporting - Wardelmann, Eva; Haas, R. L.; Bovée, J. V. M. G.; Terrier, Ph; Lazar, A.; Messiou, C.; LePechoux, C.; Hartmann, W.; Collin, F.; Fisher, C.; Mechtersheimer, Gunhild; DeiTos, A. P.; et al. (European journal of cancer, 2016)
At present, there is not a commonly used and generally accepted standardized approach for the pathologic evaluation of pretreated soft tissue sarcomas. Also, it is still unclear whether the cut-off for prognostic relevance is similar in the many different histological subtypes of STS. This manuscript, produced by a European Organization for Research and Treatment of Cancer - Soft Tissue and Bone Sarcoma Group (EORTC-STBSG) endorsed task force, aims to propose standardization of the pathological examination process and the reporting of STS resection specimens after neoadjuvant radio- and/or chemotherapy.